Colorado water, April 2003 - Flanagan, Marian, author; Jacobson, Alex, author; Miller, Shirley, editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2003)
Newsletter of the Water Center at Colorado State University.
The scope of the newsletter is devoted to enhancing communication between Colorado water users and managers and faculty at the research universities in the state.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado